Implementation of E-Module Stoiciometry Based on Kvisoft Flipbook Maker for Increasing Understanding Study Learning Concepts of Class X Senior High School - Hayati Nufus; Susilawati Susilawati; Roza Linda (Journal of Educational Sciences, 2020)
Referring to the current era of globalization, which refers the era of revolution 4.0, the use of today's technology in the learning process can be utilized. One of them is in applying ordinary modules into e-modules. The purpose of this study is the use of e-module stoichiometry based on Kvisoft flipbook maker to see the magnitude of the increase in students' understanding of the concept of stoichiometry. The research design used was a pre-experiment with a pretest-posttest design using one class as an experimental class. The sample in this study were students of the Madrasah Aliyah Negeri (MAN) 2 Pekanbaru class X KI 2. The results obtained were an increase in students' understanding of the concept from before using the e-module based on the koftoft flipbook maker with an average value of 40.2. After using Kvisoft flipbook maker based e-module the average value increased to 92.48. Large increase obtained by 0.83 with the category of moderate increase.